Policy spillovers from climate actions to energy poverty: International evidence - Jun Li; Jiajia Li; Kun Guo; Qiang Ji; Dayong Zhang (Humanities and Social Sciences Communications, 2024)
Policies to address climate change have been implemented worldwide in recent years. The core of these policies is to control greenhouse gas (GHG) emissions, which primarily stem from the consumption of fossil fuels. Consequently, the implementation of climate policies can affect other energy-related issues, such as energy poverty, a critical element of the UN Sustainable Development Goals (SDGs). This paper uses cross-country data from 2000 to 2020 to study the possible policy spillovers from climate actions to energy poverty. We show that a spillover effect does exist. In other words, a higher number of climate policies is associated with a lower level of energy poverty. The spillover is realized through improvements in energy efficiency, the promotion of renewable energy, and support for innovations. In addition, legislative policies are found to have stronger spillover effects. While the overall policy effects are positive for executive policies, regulations tend to have negative impacts on energy development. There is also evidence demonstrating heterogeneous effects between long-term and short-term policies, and between developed and developing countries. Discovering this spillover effect gives extra motivation for countries to adopt climate policies and actively seek synergies in achieving broader sustainable goals.
Keywords: 330; economics; environmental studies; social policy